Are foreign investors locusts? The long-term effects of foreign institutional ownership - Bena, Jan; Ferreira, Miguel A; Matos, Pedro; Pires, Pedro (Journal of Financial Economics, 2017)
This paper challenges the view that foreign investors lead firms to adopt a short-term orientation and forgo long-term investment. Using a comprehensive sample of publicly listed firms in 30 countries over the period 2001–2010, we find instead that greater foreign institutional ownership fosters long-term investment in tangible, intangible, and human capital. Foreign institutional ownership also leads to significant increases in innovation output. We identify these effects by exploiting the exogenous variation in foreign institutional ownership that follows the addition of a stock to the MSCI indexes. Our results suggest that foreign institutions exert a disciplinary role on entrenched corporate insiders worldwide.